The Effect of Prophylactic Polishing Pastes on Surface Roughness of Indirect Restorative Materials - Esra Can Say; Haktan Yurdagüven; Özlem Malkondu; Nimet Ünlü; Mübin Soyman; Ender Kazazoğlu (The Scientific World Journal)
The purpose of this study was to evaluate the influence of prophylactic polishing pastes (PPP; Detartrine (DT), Topex (TP)) on surface roughness (Ra) of indirect composites (IRC; Tescera (TES), Gradia (GRD), and Estenia C&B (EST)), a glass ceramic (Empress 2 layering (E2)), and a leucite reinforced glass ceramic (Empress Esthetic (EE)) with two different (glazed (G); polished (P)) surface preparations. A total of 90 IRC and 120 ceramic discs, 8 mm in diameter and 2 mm thick, were prepared. E2 and EE specimens were randomly divided into two groups (n=30). One group was glazed (GE2; GEE), while the other group was polished (PE2; PEE) the same as the IRCs. The specimens in each group were subsequently divided into three subgroups: control (C), DT, and TP. Ra (μm) was evaluated with a profilometer. Data were analyzed by Kruskal Wallis, followed by the Dunn's multiple comparison tests P<0.05. DT and TP resulted in significant surface roughening for TES, GRD, and EST, while no significant differences were detected between DT and TP P>0.05. PE2 and PEE were not affected by DT or TP P>0.05, while GE2 and GEE exhibited significant roughening after TP P<0.05. Surface roughness of IRCs and glazed ceramics can be affected by PPP applications.